FABP4 and Cardiovascular Events in Peripheral Arterial Disease. (May 2018) - Höbaus, Clemens; Herz, Carsten Thilo; Pesau, Gerfried; Wrba, Thomas; Koppensteiner, Renate; Schernthaner, Gerit-Holger
Fatty acid–binding protein 4 (FABP4) is a possible biomarker of atherosclerosis. We evaluated FABP4 levels, for the first time, in patients with peripheral artery disease (PAD) and the possible association between baseline FABP4 levels and cardiovascular events over time. Patients (n = 327; mean age 69 ± 10 years) with stable PAD were enrolled in this study. Serum FABP4 was measured by bead-based multiplex assay. Cardiovascular events were analyzed by FABP4 tertiles using Kaplan-Meier and Cox regression analyses after 5 years. Serum FABP4 levels showed a significant association with the classical 3-point major adverse cardiovascular event (MACE) end point (including death, nonlethal myocardial infarction, or nonfatal stroke) in patients with PAD ( P = .038). A standard deviation increase of FABP4 resulted in a hazard ratio (HR) of 1.33 (95% confidence interval [95% CI]: 1.03-1.71) for MACE. This association increased (HR: 1.47, 95% CI: 1.03-1.71) after multivariable adjustment ( P = .020). Additionally, in multivariable linear regression analysis, FABP4 was linked to estimated glomerular filtration rate ( P < .001), gender ( P = .005), fasting triglycerides ( P = .048), and body mass index ( P < .001). Circulating FABP4 may be a useful additional biomarker to evaluate patients with stable PAD at risk of major cardiovascular complications.